Comparative Lipid Peroxidation and Apoptosis in Embryo‐Larval Zebrafish Exposed to 3 Azole Fungicides, Tebuconazole, Propiconazole, and Myclobutanil, at Environmentally Relevant Concentrations. (4th June 2019) - Kumar, N.; Awoyemi, O.; Willis, A.; Schmitt, C.; Ramalingam, L.; Moustaid‐Moussa, N.; Crago, J.
Abstract: Azole fungicides have entered the aquatic environment through agricultural and residential runoff. In the present study, we compared the off‐target toxicity of tebuconazole, propiconazole, and myclobutanil using embryo‐larval zebrafish as a model. The aim of the present study was to investigate the relative toxicity of tebuconazole, propiconazole, and myclobutanil using multiple‐level endpoints such as behavioral endpoints and enzymatic and molecular biomarkers associated with their mode of action. Zebrafish embryos were exposed to azoles at environmentally relevant and high concentrations, 0.3, 1.0, and 1000 µg/L, starting at 5 h postfertilization (hpf) up to 48 hpf, as well as 5 d postfertilization (dpf). Relative mRNA expressions of cytochrome P450 family 51 lanosterol‐14α‐demethylase, glutathione S ‐transferase, caspase 9, phosphoprotein p53, and BCL2‐associated X protein were measured to assess toxicity attributable to fungicides at the mRNA level, whereas caspase 3/7 (apoptosis) and 3, 4‐methylene​dioxy​amphetamine (lipid peroxidation) levels were measured at the enzymatic level. Furthermore, mitochondrial dysfunction was measure through the Mito Stress test using the Seahorse XFe24 at 48 hpf. In addition, light to dark movement behavior was monitored at 5 dpf using Danio Vision® to understand adverse effects at the organismal level. There was no significant difference in the light to dark behavior with exposure to azoles compared to controls. The molecular biomarkers indicated that propiconazole and myclobutanil induced lipid peroxidation, oxidative stress, and potentially apoptosis at environmentally relevant concentrations (0.3 and 1 µg/L). The results from the mitochondrial respiration assay indicated a slight decrease in spare respiratory capacity with an acute exposure (48 hpf) to all 3 azoles at 1000 µg/L. Based on the present results, propiconazole and myclobutanil are acutely toxic compared to tebuconazole in aquatic organisms at environmentally relevant concentrations. Environ Toxicol Chem 2019;38:1455–1466. © 2019 SETAC Abstract : The present study concludes that tebuconazole is least toxic to aquatic organisms compared to myclobutanil and propiconazole under similar exposure conditions. BAX = BCL2‐associated X protein; Casp9 = caspase 9; GST = glutathione S ‐transferase; LPO = lipid peroxidation; p53 = phosphoprotein p53.